Pengaruh Type Hedonic Shopping Motivation terhadap Keputusan Berkunjung Tourist Shopper - Yustisia P. Mbulu; Raisya Kurnia Maidina; Nungky Puspita (Fakultas Pariwisata Universitas Pancasila, 2017)
Grand Indonesia Shopping Town is a premium mall offering shopping experience that includes apparels and clothings including internationally renowned brands, restaurants and entertainment options. With modern architecture and design, the Mall is enjoyed by a wide range of consumers. .This study aims to look at the influence of hedonic shopping motivation on the decision to visit among the tourist shoppers at Grand Indonesia Shopping Town. The method used in this research is quantitative descriptive using Structural Equation Modelling (SEM) with a sample of 100 respondents. Results from this study found that out of six variables that constitute hedonic shopping motivation, only two of which have a significant influence on the decision to visit, namely, the idea of shopping (***) and social shopping (,006).